Possible mechanism of adhesion in a mica supported phospholipid bilayer - Pertsin, Alexander; Grunze, Michael (The journal of chemical physics, 2014)
Phospholipid bilayers supported on hydrophilic solids like silica and mica play a substantial role in fundamental studies and technological applications of phospholipid membranes. In both cases the molecular mechanism of adhesion between the bilayer and the support is of primary interest. Since the possibilities of experimental methods in this specific area are rather limited, the methods of computer simulation acquire great importance. In this paper we use the grand canonical Monte Carlo technique and an atomistic force field to simulate the behavior of a mica supported phospholipid bilayer in pure water as a function of the distance between the bilayer and the support. The simulation reveals a possible adhesion mechanism, where the adhesion is due to individual lipid molecules that protrude from the bilayer and form widely spaced links with the support. Simultaneously, the bilayer remains separated from the bilayer by a thin water interlayer which maintains the bilayer fluidity.